Rey–Osterrieth Complex Figure – copy and immediate recall (3 minutes): Normative data for Spanish-speaking pediatric populations - Arango-Lasprilla, JC; Rivera, D; Ertl, M M; Muñoz Mancilla, J M; García-Guerrero, CE; Rodriguez-Irizarry, W; Aguayo Arelis, A; Rodríguez-Agudelo, Y; Barrios Nevado, MD; Vélez-Coto, M; Yacelga Ponce, TP; Rigabert, A; et al. (NeuroRehabilitation, 2017)
OBJECTIVE: To generate normative data for the Rey-Osterrieth Complex Figure (ROCF) in Spanish-speaking pediatric populations. METHOD: The sample consisted of 4,373 healthy children from nine countries in Latin America (Chile, Cuba, Ecuador, Guatemala, Honduras, Mexico, Paraguay, Peru, and Puerto Rico) and Spain. Each participant was administered the ROCF as part of a larger neuropsychological battery. The ROCF copy and immediate recall (3 minutes) scores were normed using multiple linear regressions and standard deviations of residual values. Age, age2, sex, and mean level of parental education (MLPE) were included as predictors in the analyses. RESULTS: The final multiple linear regression models showed main effect for age on copy and immediate recall scores, such that scores increased linearly as a function of age. Age2 affected ROCF copy score for all countries, except Puerto Rico; and ROCF immediate recall scores for all countries, except Chile, Guatemala, Honduras, Paraguay, and Puerto Rico. Models indicated that children whose parent(s) had a MLPE >12 years obtained higher scores compared to children whose parent(s) had a MLPE≤12 years for Chile, Puerto Rico, and Spain in the ROCF copy, and Paraguay and Spain for the ROCF immediate recall. Sex affected ROCF copy and immediate recall score for Chile and Puerto Rico with girls scoring higher than boys. CONCLUSIONS: This is the largest Spanish-speaking pediatric normative study in the world, and it will allow neuropsychologists from these countries to have a more accurate approach to interpret the ROCF Test in pediatric populations.
Keywords: Rey–Osterrieth Complex Figure; neuropsychology; spanish-speaking populations; pediatric population; JCR; Scopus